2021
DOI: 10.1007/s00404-021-05966-3
|View full text |Cite
|
Sign up to set email alerts
|

The potential association between a new angiogenic marker fractalkine and a placental vascularization in preeclampsia

Abstract: Purpose Impaired angiogenesis is one of the most common findings in preeclamptic placentas. A new angiogenetic role of fractalkine (CX3CL1) is recently recognized apart from inflammatory activity. In this study, a link between CX3CL1 and the development of placental vasculature in preeclampsia was examined. Methods The study comprised 52 women allocated to Group 1 (normotensive, n = 23) and Group 2 (preeclampsia, n = 29). In each group Doppler parameters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
5
1
Order By: Relevance
“…Consistent with this, we found that maternal serum fractalkine concentration was higher in the FGR group than in healthy controls. In previous studies, maternal serum fractalkine concentrations were found to be higher in cases with FGR secondary to preeclampsia during pregnancy, and it was determined that the increase in placental fractalkine expression showed a positive correlation with the severity of FGR (14,23). However, we could not find a relationship between FGR severity and maternal serum fractalkine concentrations in our study.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Consistent with this, we found that maternal serum fractalkine concentration was higher in the FGR group than in healthy controls. In previous studies, maternal serum fractalkine concentrations were found to be higher in cases with FGR secondary to preeclampsia during pregnancy, and it was determined that the increase in placental fractalkine expression showed a positive correlation with the severity of FGR (14,23). However, we could not find a relationship between FGR severity and maternal serum fractalkine concentrations in our study.…”
Section: Discussioncontrasting
confidence: 82%
“…In different studies, it has been shown that metalloproteases (ADAM10 and ADAM17) detected in syncytiotrophoblasts, which mediate the shedding, are interestingly increased in preeclampsia (20,21). Consistent with this information, it is not surprising that in subsequent studies, serum fractalkine concentrations were found to be higher in women whose pregnancy was complicated with preeclampsia than in normotensive healthy pregnant women (22,23).…”
Section: Discussionmentioning
confidence: 69%
“…Other trials have denoted that pregnant women with pre-eclampsia present an overexpression of fractalkine, coinciding with poor pregnancy outcomes [ 108 ]. Recently, elevated levels of fractalkine in maternal serum in pre-eclampsia have been described [ 109 ]. Moreover, CX3CL1 chemoattractant and adhesive properties breeding inflammation and angiogenesis processes are especially upregulated by inflammatory conditions such as diabetic placenta.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it may play a role in the proinflammatory trophoblast-monocyte interaction (Siwetz et al, 2015;Nonn et al, 2019). Szewczyk et al (2021) discovered considerably higher CX3CL1 serum levels and placental expression in PE patients and a negative correlation with the vascular/extravascular tissue index. The authors postulated that severe underdevelopment of the placental vascular network in PE is associated with alterations in CX3CL1 expression and distribution.…”
Section: Open Accessmentioning
confidence: 99%
“…Previous research has demonstrated the critical roles that maternal immune regulators, such as the chemokines CXC and CX3CL1 (fractalkine), play in the interaction between PE and their surroundings ( Liu et al, 2015 ; Lei et al, 2019 ; Szewczyk et al, 2021 ). Furthermore, Liu et al (2022) indicated the connection between GDM and CXC chemokines.…”
Section: Introductionmentioning
confidence: 99%